Observation of correlated azimuthal anisotropy Fourier harmonics in pp and pPb collisions at the LHC - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2017)
The azimuthal anisotropy Fourier coefficients (v(n)) in 8.16 TeV p + Pb data are extracted via long-range two-particle correlations as a function of the event multiplicity and compared to corresponding results in pp and PbPb collisions. Using a four-particle cumulant technique, v(n) correlations are measured for the first time in pp and p + Pb collisions. The v(2) and v(4) coefficients are found to be positively correlated in all collision systems. For high-multiplicity p + Pb collisions, an anticorrelation of v(2) and v(3) is observed, with a similar correlation strength as in PbPb data at the same multiplicity. The new correlation results strengthen the case for a common origin of the collectivity seen in p + Pb and PbPb collisions in the measured multiplicity range.

Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq)

Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)

Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro (FAPERJ)

Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP)

Swiss Funding Agencies (Switzerland)

Academy of Finland (Finland)

MSIP (Republic of Korea)

NRF (Republic of Korea)

COLCIENCIAS (Colombia)
Keywords: ddc:620; correlation: two-particle; p p: scattering; General Physics; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; [PHYS.NEXP] Physics [physics]/Nuclear Experiment [nucl-ex]; FLOW; Physics, Multidisciplinary; General Physics and Astronomy; FOS: Physical sciences; [PHYS.NEXP]Physics [physics]/Nuclear Experiment [nucl-ex]; Flow.; nucl-ex; High Energy Physics - Experiment; Nuclear collisions; FLOW; Physics and Astronomy (all); High Energy Physics - Experiment (hep-ex); [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; angular distribution: anisotropy; Nuclear collisions; azimuthal anisotropy, p+Pb; Nuclear Experiment (nucl-ex); p nucleus: scattering; Nuclear Experiment; Engineering & allied operations; Multidisciplinary; info:eu-repo/classification/ddc/550; Science & Technology; Physical Sciences; Anisotropy; Binary alloys; Fourier analysis; Tellurium compounds; CMS; hep-ex; Physics; multiplicity: high; GeV-cms/nucleon; long-range; CERN LHC Coll; flow; Hadron, Hadron collisions (experiments); Physical Sciences; info:eu-repo/classification/ddc/620; experimental results